Investigating the Prevalence of Sleep Disorder and the Impact of Sweet Almond on the Quality of Sleep in Students of Tehran, Iran - Jafar GHAFARZADEH; Khosro SADEGHNIIAT-HAGHIGHI; Omid SADEGHPOUR; Samaneh AKBARPOUR; Farshad AMINI-BEHBAHANI (Tehran University of Medical Sciences, 2019)
Background: Insomnia is an important problem in medical sciences students and has implications for their educational progress. The current study aimed to estimate the prevalence of sleep disorders and investigating the impact of sweet almond on quality of sleep in students of the Tehran University of Medical Sciences (TUMS), Tehran, Iran who live in dormitories. Methods: This is a before-after study conducted in 2017. At first, using the ISI questionnaire prevalence of sleep disorders was determined. Sweet almond was the study intervention. Each day, 10 almonds were given to 446 students for 14 d. At the end of the second week, again ISI questionnaire was filled. SPSS was used to analyze data. The McNemar, Wilcoxson Signed Ranks, and Repeated Measures tests were used. Results: Out of 442 participants, 217 (49.1%) were female. Before intervention, 343 (77.6%) had insomnia and 99 (22.4%) had normal sleep. After intervention, 306 (69.2%) had insomnia and 136 (30.8%) had normal sleep. Having sweet almond for two weeks is associated with reducing insomnia (P<0.05). Investigating the almond impact in different categories also showed that it has a reducing impact on severe, mild, weak and normal sleep categories (P<0.05). Conclusion: Sweet almond has impacts on quality of sleep of those students of the TUMS that are living in dormitories. Intervention programs to improve quality of sleep are necessary and with regard to the high prevalence of insomnia, students must be protected, guided and consulted.